Hollow agarose microneedle with silver coating for intradermal surface-enhanced Raman measurements : a skin-mimicking phantom study - Yuen, Clement (2015)
Human intradermal components contain important clinical information beneficial to the field of immunology and disease diagnosis. Although microneedles have shown great potential to act as probes to break the human skin barrier for the minimally invasive measurement of intradermal components, metal microneedles that include stainless steel could cause the following problems: (1) sharp waste production, and (2) contamination due to reuse of microneedles especially in developing regions. In this study, we fabricate agarose microneedles coated with a layer of silver (Ag) and demonstrate their use as a probe for the realization of intradermal surface-enhanced Raman scattering measurements in a set of skin-mimicking phantoms. The Ag-coated agarose microneedle quantifies a range of glucose concentrations from 5 to 150 mM inside the skin phantoms with a root-mean-square error of 5.1 mM within 10 s. The needle is found enlarged by 53.9% after another 6 min inside the phantom. The shape-changing capability of this agarose microneedle ensures that the reuse of these microneedles is impossible, thus avoiding sharp waste production and preventing needle contamination, which shows the great potential for safe and effective needle-based measurements.